Metodologias para uma assistência técnica e extensão rural equitativa - MARQUES, Zelia Vanuza (2020)
This work aims to contribute with reflections on equity in the context of the public policy of Technical Assistance and Rural Extension - ATER for family agriculture in Brazil and to propose a methodological tool for systematization of ATER experiences with a gender focus. The research was structured from a research process referenced by the theoretical and methodological contributions of the qualitative action research in which extensionists and beneficiaries of Technical Assistance and Rural Extension - ATER participated, linked to the actions of the Technical Assistance and Rural Extension Company of the State of Pará - EMATER-PA. Initially, we sought to reflect on the contributions of popular education and agroecology to equitable ATER, through the identification of contributions in national scientific productions on Popular Education and Agroecology. At this stage, the source of the research was for virtual access to the Journal Portal of the Coordination for the Improvement of Higher Education Personnel - CAPES from 2012 to 2017. As results, the bibliographical research was identified that the valorization of citizenship and the promotion of sustainable rural development based on the principles of Agroecology, the democratic, participatory methodological approaches and the recognition of the plurality and diversity of the categories that make up family agriculture are contributions of Popular Education and Agroecology for the resignification of the theoretical and methodological bases of the diffusionist ATER public policy for a fair ATER the construction of institutionalization. In relation to the field research the analysis of documents, it made it possible to identify that the actions of ATER have been carried out together with a diversity of public and the action research process that involved an exercise of Systematization of Experiences, revealed that in the realities researched there is a process of disruption with the stereotypes of gender and generation, being identified the approach of productive technical themes social and economic policies, including guidelines for access to public policies. Finally, it was concluded that the methodology of Systematization of Experiences experienced in the research can mean a pedagogical political strategy with potential to contribute to the reflection on gender approach and other inequalities in the context of ATER and thus contribute to the consolidation of the equitable approach of ATER recommended by the National Policy of ATER